Assisting the Production Process of Kefir Milk Soap in the Women's Livestock Group, Blender Village, Kebon Pedes, Bogor - Aprilla Ayu Wulandari; Dhigna Luthfiyani Citra Pradana; Anisah Anisah (Institute for Research and Community Services, 2020)
This community-empowerment activity was conducted in Blender Village, a cattle rancher village. The community makes a living from raising cattle and selling cow milk. The cow milk is only sold in the surrounding area, and therefore is insufficient to sustain the livelihood of the villagers who are low in economic status. The aim of this community-empowerment activity in the production process of Kefir Milk Soap in the Blender Women's Livestock Group (WLG) was to help the Blender village community able to produce kefir soap, which can later give them additional income. Kefir soap is a kind of soap made from high-quality pure cow milk that is fermented beforehand in its process. Fermentation is done by mixing the milk with kefir seeds and leave it alone for 2-4 days until two parts of viscosity separation of fermented milk are formed. The thick part is selected and mixed with other ingredients (using the hot heating/cooking) method or cold method). Next, it is put into soap moulds and is left for 1-2 weeks before being used. The community-empowerment activity helped the WLG in producing kefir soap and it is hoped that they can train other residents. By being able to make kefir soap, it is hoped that the residents of Blender Village can have additional income and improve their livelihood.